2011
DOI: 10.1186/1758-3284-3-17
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound, clinical and scintigraphyc parameters to predict malignancy in thyroid nodule

Abstract: BackgroundThis study aimed to evaluate clinical, laboratory, ultrasound (US) and scintigraphyc parameters in thyroid nodule and to develop an auxiliary model for clinical application in the diagnosis of malignancy.MethodsWe assessed 143 patients who were surgically treated at a single center, 65% (93) benign vs. 35% (50) malignant lesions at final histology (1998-2008). The clinical, laboratory, scintigraphyc and US features were compared and a prediction model was designed after the multivariate analysis.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 27 publications
(54 reference statements)
5
23
0
5
Order By: Relevance
“…Furthermore, it was observed that as the solid component of the nodule increases (mixed echogenicity), the risk of malignancy increases. The presence of micro-calcification was observed to significantly increase the risk of malignancy in the nodule, similar to the literature (9,10,(12)(13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Furthermore, it was observed that as the solid component of the nodule increases (mixed echogenicity), the risk of malignancy increases. The presence of micro-calcification was observed to significantly increase the risk of malignancy in the nodule, similar to the literature (9,10,(12)(13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 76%
“…Micro-calcification, not containing a cystic component and heterogeneous internal structure have been reported as important USG findings in the diagnosis of thyroid carcinoma in many studies (9,10). In our study, the comparison of pre-operative USG findings and main specimen pathology results revealed a significantly higher risk of malignancy in solid hypo echoic nodules compared to others (11)(12)(13)(14). Furthermore, it was observed that as the solid component of the nodule increases (mixed echogenicity), the risk of malignancy increases.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Türkiye'de yapılan çalışmalarda, bu oran yaklaşık %2,8 olarak bulunmuştur (9). Ancak USG'nin gelişmesi ile tiroid nodül insidansının %16-67 olduğu görülmüştür (10). Bu nodüllerin birçoğu, non-palpabl (%90) ve benign karakterdedir (11,12).…”
Section: Discussionunclassified
“…Further cytological examination is needed for nodules having a hypoechoic appearance with one or other suspicious findings (1,2). In a study, it was reported that the coexistence of age at 39 years or above, an irregular margin, microcalcification, and the nodule being larger than 2 cm could predict malignancy at an accuracy rate of 81.7% (11). Moreover, it was specified that the specificity of a spongiform appearance for demonstrating a benign nodule was 99.7% and the negative predictive value for malignancy was 98.5%.…”
Section: Thyroid Usgmentioning
confidence: 99%